Is local recurrence higher among patients who downstage to breast conservation after neoadjuvant chemotherapy?. Issue 3 (1st October 2021) - Mamtani, Anita; Sevilimedu, Varadan; Le, Tiana; Morrow, Monica; Barrio, Andrea V.
Abstract : Background: In early studies, local recurrence (LR) rates were higher after neoadjuvant chemotherapy (NAC) in comparison with upfront surgery. Modern outcomes are uncertain, particularly among those who are initially breast‐conserving surgery–ineligible (BCSi) and downstage to being breast‐conserving surgery–eligible (BCSe). Methods: Among patients with cT1‐3 breast cancer treated from 2014 to 2018 who were BCSe after NAC, clinicopathologic characteristics and LR were compared between initially BCSe patients and BCSi patients who downstaged. Breast‐conserving surgery (BCS) eligibility was determined prospectively. Results: Among 685 patients, 243 (35%) were BCSe before and after NAC and had BCS; 282 (41%) were BCSi before NAC, downstaged to BCSe, and had BCS; and 160 (23%) were BCSi before NAC, downstaged to BCSe, and chose mastectomy. The median age was 52 years, and most cancers were cT1‐2 (84%), cN+ (61%), and human epidermal growth factor receptor 2–positive (HER2+; 38%) or triple‐negative (34%). Those who were BCSe before NAC had a lower cT stage, whereas those who chose mastectomy were younger ( P < .05). NAC was usually ACT (doxorubicin, cyclophosphamide, and a taxane)‐based (92%), 99% of HER2+ patients received dual blockade, and 99% of BCS patients received adjuvant radiation. At a median follow‐up of 35 months, 22 patients (3.2%) had developed LR. The Kaplan‐Meier 4‐year LR rates were not different among the groups (1.9% for those who were BCSe before and after NAC, 6.3% for those who downstaged to being BCSe and underwent BCS, and 2.7% for those who downstaged and underwent mastectomy; P = .17). Conclusions: LR rates are low after NAC and BCS, even among BCSi patients who downstage, and they are not improved in patients who downstage and choose mastectomy. Mastectomy can be safely avoided in BCSi patients who downstage with NAC. Abstract : In a large cohort of cT1‐3 patients with invasive breast cancer treated with neoadjuvant chemotherapy (n = 685), this study investigates whether local recurrence rates are higher in breast‐conserving surgery (BCS)–ineligible patients who downstage to BCS in comparison with those who are initially BCS‐eligible and undergo BCS and those who are BCS‐ineligible, downstage, and choose mastectomy. Four‐year local recurrence rates after neoadjuvant chemotherapy and BCS are low among those who downstage (6.3%), and they are not improved in patients who choose mastectomy; this suggests that such patients may be safely treated with BCS.